2007
DOI: 10.1242/jcs.005306
|View full text |Cite
|
Sign up to set email alerts
|

RhoA-mediated apical actin enrichment is required for ciliogenesis and promoted by Foxj1

Abstract: Programs that direct cellular differentiation are dependent on the strict temporal expression of regulatory factors that can be provided by Rho GTPases. Ciliogenesis is a complex sequence of events involving the generation and docking of basal bodies at the apical membrane, followed by ciliary axoneme generation. Although a cilia proteome has been assembled, programs that direct ciliated cell differentiation are not well established, particularly in mammalian systems. Using mouse primary culture airway epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
176
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(194 citation statements)
references
References 69 publications
12
176
0
2
Order By: Relevance
“…Studies of ciliogenesis in the quail oviduct showed that localization of basal bodies to the apical cell domain depends on actin dynamics 35 . In line with this, ciliogenesis is defective in Foxj1 mutant mice, due to abnormal basal body anchoring to the actin-based apical cytoskeleton, and failure of RhoA-mediated apical actin enrichment [44][45][46][47] . The hypothesis that PCP signaling regulates apical actin network formation required for docking of basal bodies and normal ciliogenesis predicts that mutations in other genes that control PCP in mice should similarly lead to cilia dysfunction and hydrocephalus.…”
mentioning
confidence: 66%
“…Studies of ciliogenesis in the quail oviduct showed that localization of basal bodies to the apical cell domain depends on actin dynamics 35 . In line with this, ciliogenesis is defective in Foxj1 mutant mice, due to abnormal basal body anchoring to the actin-based apical cytoskeleton, and failure of RhoA-mediated apical actin enrichment [44][45][46][47] . The hypothesis that PCP signaling regulates apical actin network formation required for docking of basal bodies and normal ciliogenesis predicts that mutations in other genes that control PCP in mice should similarly lead to cilia dysfunction and hydrocephalus.…”
mentioning
confidence: 66%
“…5b, arrows). In addition, the microvilli, which interspaced the axonema, appeared to be reduced in length as well as in number, compared with the WT samples from the same litter, reminiscent of actin organization or Rho GTPase activity defect 32,33 . Thus, in mutant cells basal bodies multiply normally but fail to migrate apically, suggesting a defect in transport and/or docking at the apical membrane.…”
Section: Cyld Interacts With Cap350 At the Centrosome/basal Bodiesmentioning
confidence: 97%
“…The forkhead transcription factor Foxj1 is required for ciliogenesis and also involved in the organization of the apical membrane. 39 In the differentiated pseudostratified epithelium, Foxj1 is present and expressed at the same level in most cell nuclei of the epithelium. In ␣BTX-exposed cultures, Foxj1 is still present in the basal progenitor cells of the epithelium, but its expression is much lower in the intermediate cells and finally absent in the upper part of the epithelium ( Figure 7D).…”
Section: The ␣7 Nachr Is Involved In the Differentiation Pathway Of Tmentioning
confidence: 99%